About the classification of heart failure - A. S. Galyavich; S. V. Nedogoda; G. P. Arutyunov; Yu. N. Belenkov (Российский кардиологический журнал, 2023)
The article discusses the classification of heart failure (HF). A novel HF classification and its advantages over the existing ones are shown. Variants of approximate diagnoses are given in accordance with the novel HF classification.